2020
DOI: 10.1089/g4h.2019.0082
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Motivational Differences Between Young and Older Adults When Playing an Exergame

Abstract: Currently, exergames are used by different age groups for both recreational and training/rehabilitation purposes. However, little is known about how to design exergames so that they are motivating for specific age groups and health outcomes. Objective: In this paper, we compare motivational factors between healthy young and older adults by analyzing their assessments of the same balance training exergame. Materials and Method: We performed a laboratory-based assessment of a custom-made balance training exergam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…This high score may also be attributed to a positive perspective on the potential positive effect on motor function. In addition to enjoyment, a positive impact on health effects has been shown to affect motivation to exercise in older people [33]. Previous work has reported that varying the difficulty of the task to suit the disability has positive effects on motivating users and improving their upper extremity function [34].…”
Section: Discussionmentioning
confidence: 99%
“…This high score may also be attributed to a positive perspective on the potential positive effect on motor function. In addition to enjoyment, a positive impact on health effects has been shown to affect motivation to exercise in older people [33]. Previous work has reported that varying the difficulty of the task to suit the disability has positive effects on motivating users and improving their upper extremity function [34].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the population, different factors determine how more autonomous motivation can be promoted. A small case-control study with a balance exergaming platform evaluated that “older adults were more intrinsically motivated by the joy of playing and extrinsically motivated by the perceived health effects (physical and cognitive), with less regard for the in-game rewards” ( Subramanian et al, 2019 ). For patients with NCDs specifically, a new theoretical model, the ‘PHYT in dementia’ ( Di Lorito et al, 2019 ), was recently introduced.…”
Section: Case Studymentioning
confidence: 99%
“…Motivations can change with age: fantasy is a powerful motivational factor in younger children [27], whereas competition and challenge-related motives are stronger in older children and adolescents [69]. Young adults are more motivated by rewarding experiences, while older adults are more inspired by perceived benefits to their health [73]. Young adults tend to prefer visually appealing graphics and music that fit the theme and nature of the game, but older adults pay more attention to the feedback that helps them complete a game [73].…”
Section: Game Experience For Different Age Groupsmentioning
confidence: 99%